Perencanaan Pemanfaatan Air Blowdown Cooling Tower Untuk Supply Make Up Cooling Tower Di Bandar Udara Internasional Yogyaka.pdf - Kurniawanto, Hari; Inten Suwono, Niedya; Nabila Putri, Esa; Budi Santoso, Rahmad; Mulia Fenesa, Rama; Sidiq Muftia Jaya, Gilang (Program Studi Teknik Mekanikal Bandar Udara, 2024)
This journal aims to explore the potential utilization of cooling tower blowdown water as a source of make-up water for cooling towers at Yogyakarta International Airport. Currently, the cooling tower work system at the airport relies on water supply from STP and PDAM as an alternative source. However, the use of PDAM water can be reduced by utilizing cooling tower blowdown water which is currently discharged into the canal. In this journal, the writing team will analyze the quality of the resulting cooling tower blowdown water, including the level of contamination and water quality parameters. The methods used include water sampling, water measurement, and water treatment system design. It is hoped that by utilizing cooling tower blowdown water as a make-up supply for cooling towers, it is expected to save PDAM water use, reduce wasted waste, and increase water use efficiency.